Analysis and synthesis of data on relationships between soil factors and soil erosion in South Africa - Barnard, R.O. (Robin Oxley), 1940- (University of Pretoria, 2013)
Dissertation (MInst Agrar (Land-Use Planning))--University of Pretoria, 2006.